FAKTOR INTERNAL DAN EKSTERNAL PENGARUHNYA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Kirwani, ; Ririn Wulandari, (Pendidikan Ekonomi, 2010)
The present research was intended to find out the effect of the internal and external factors on the learning results of the students. The population was the tenth graders of SMAN 2 Nganjuk, whereas the sample was the students of class X-4. The data were collected through questionnaires and documentation. The data were then analyzed with correlation and regression techniques. The results of the study showed that the internal and external factors had a significant influence on the learning results of economics subject among the students of SMAN 2 Nganjuk. It was also found that the more dominant factors are the external ones.